Life Cycle Cost Analysis of Residential Power Backup Gasoline Generators in Nigeria - B.N. Nwankwojike; J.O. Nwosu; M.O. Egwuagu (Journal of Applied Sciences and Environmental Management)
This study involves life cycle cost analysis of portable gasoline generator brands mostly used for home power back up in Nigeria to guide the citizens’ choice during acquisition. A total of two thousand six hundred and twenty electric power generating sets sampled from seventeen cities in Nigeria were evaluated by direct  observation/descriptive experimental design. The evaluation parameters include initial or procurement, operation and maintenance costs, fuel consumption rate, operation period and residual value. Results showed Tiger, Sumec, Elemax, Elepaq and Jinjing as the most patronized brands of portable gasoline generators for home power back up in Nigeria major cities while 0.8 and 2.2KVA constitute the most used power ratings of the generators. Also 0.8KVA Sumec and 2.2KVA Elemax were revealed as most cost effective due to their comparative low life cycle cost of N26, 810 and N39,820 respectively.